Manufacturing method of grain-oriented electrical steel sheet

By using machine learning to optimize annealing conditions for directional electromagnetic steel sheets, the method addresses the challenges of high manufacturing costs and coating property variations, achieving stable and excellent coating adhesion across the steel sheet.

JP7666756B2Active Publication Date: 2025-04-22JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024550645
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-10
Filing Date
2024-04-23
Publication Date
2025-04-22
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

Existing methods for manufacturing directional electromagnetic steel sheets with excellent coating properties over their entire length and width face challenges such as high manufacturing costs, insufficient effectiveness, and variations in coating properties due to fluctuations in annealing conditions and surface roughness.

Method used

A method involving multiple regression analysis or machine learning to optimize the annealing separator composition and finishing annealing conditions based on data from decarburizing annealing plate quality indices and forsterite coating weight contents, ensuring consistent coating adhesion across the steel sheet.

Benefits of technology

This approach enables the stable production of directional electromagnetic steel sheets with excellent coating properties over the entire length and width, improving adhesion and magnetic properties while reducing manufacturing costs and variations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666756000017
    Figure 0007666756000017
  • Figure 0007666756000018
    Figure 0007666756000018
  • Figure 0007666756000019
    Figure 0007666756000019
Patent Text Reader

Abstract

This method for manufacturing a grain-oriented electrical steel sheet comprises: acquiring data of a decarburization annealed sheet quality index and a finishing annealing condition of a product sheet; acquiring data of an O coating amount and a Ti + V + Zr + Nb coating amount contained in a forsterite coating film of the product sheet; performing multiple regression analysis or machine learning using an actual value of each of the coating amounts as an objective variable and actual values of the decarburization annealed sheet quality index, an annealing separation agent composition, and the finishing annealing condition as explanatory variables, to create a prediction model for each coating amount; and using the prediction model for each coating amount to set, in accordance with the value of the decarburization annealed sheet quality index at each position (m, n) when the steel sheet is divided by i in the longitudinal direction and by j in the width direction, the annealing separation agent composition and the finishing annealing condition so that the O coating amount and the (Ti + V + Zr + Nb coating amount) / O coating amount at each position (m, n) are within a range determined by coating film adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a grain-oriented electrical steel sheet having excellent coating properties over its entire length and width. [Background technology]

[0002] Grain-oriented electrical steel sheets are soft magnetic materials mainly used for the iron cores of transformers, etc., and are required to have excellent magnetic properties, i.e., low iron loss and high magnetic flux density. Such grain-oriented electrical steel sheets are manufactured by hot rolling a material containing inhibitor-forming components such as MnS, MnSe, or AlN, subjecting it to hot-rolled sheet annealing as necessary, subjecting it to cold rolling once or two or more times with intermediate annealing in between, subjecting it to decarburization annealing, coating the steel sheet surface with an annealing separator mainly composed of MgO, and then subjecting it to finish annealing.

[0003] In the above-mentioned finish annealing, the oxide film mainly composed of SiO2 formed in the decarburization annealing reacts with the annealing separator mainly composed of MgO to form a forsterite film. This forsterite film not only imparts insulation to the steel sheet surface, but also improves the magnetic properties of the steel sheet by imparting tensile stress due to its low thermal expansion.

[0004] Therefore, in order to produce a grain-oriented electrical steel sheet with excellent magnetic properties, it is extremely important to form a forsterite coating that has excellent coating properties, i.e., has high adhesion over the entire length and width of the steel sheet.

[0005] On the other hand, since the decarburization annealing is a continuous annealing in a highly oxidizing atmosphere, the oxidizing property in the furnace is likely to vary, and the quality of the decarburization annealed sheet, such as the amount and shape of the oxide film, is likely to vary. Furthermore, when variations occur in the composition and roughness of the steel sheet surface in the process prior to decarburization annealing, the formation of the oxide film may also vary.

[0006] In addition, since the finish annealing is batch annealing in a coil shape, temperature unevenness is likely to occur within the coil, which tends to cause variations in the coating properties.

[0007] To address these problems, Patent Document 1 proposes a technique in which the components of an annealing separator are changed and applied in the longitudinal and transverse directions of a steel sheet.

[0008] Conventionally, the coating adhesion of the forsterite coating has been evaluated by a bending peeling test. However, since this bending peeling test is a destructive test, it is impossible to measure the properties of the entire product. Therefore, even though the coating properties are prone to variation as described above, there is a problem in that it is not possible to evaluate the coating adhesion over the entire length and width while taking such variation into account.

[0009] To address this problem, Patent Document 2 proposes a technique in which light is irradiated onto the steel sheet surface and the coating adhesion is evaluated based on the brightness. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Re-table No. 2020-196773 [Patent Document 2] JP 2011-158328 A Summary of the Invention [Problem to be solved by the invention]

[0011] However, the technique described in Patent Document 1 has problems such as high production costs, insufficient effects, and still causing variations in coating properties.

[0012] Furthermore, the technique described in Patent Document 2 had the problem that even slight differences in material components or manufacturing conditions could cause the correlation between brightness and coating adhesion to shift, making it difficult to adequately evaluate coating adhesion.

[0013] The present invention advantageously solves the above-mentioned problems by providing a method for manufacturing grain-oriented electrical steel sheet that can stably produce grain-oriented electrical steel sheet with excellent coating properties by non-destructively grasping the coating properties over the entire length and width of the product steel sheet. [Means for solving the problem]

[0014] The gist of the present invention is as follows. 1. In a method for manufacturing grain-oriented electrical steel sheet, a steel material for grain-oriented electrical steel sheet is hot-rolled, and then cold-rolled once or twice or more times with intermediate annealing in between, followed by decarburization annealing, and then an annealing separator mainly composed of MgO is applied to the surface of the steel sheet, followed by finish annealing to produce a finished sheet, the method includes obtaining data on the quality index of the decarburization annealed steel sheet and the finish annealing conditions, and further obtaining data on the weight of O and the weight of Ti+V+Zr+Nb contained in the forsterite coating of the finished sheet, and using the actual values ​​of each of the weights as objective variables, and also obtaining data on the quality index of the decarburization annealed steel sheet, the annealing weight, and the final annealing conditions. A manufacturing method for grain-oriented electrical steel sheet in which a prediction model for each basis weight is created by performing multiple regression analysis or machine learning using actual values ​​of the release agent composition and the finish annealing conditions as explanatory variables, and the prediction model for each basis weight is used to set the annealing release agent composition and the finish annealing conditions so that the O basis weight and (Ti+V+Zr+Nb basis weight) / O basis weight at each position (m, n) (where 1≦m≦i, 1≦n≦j) obtained by dividing the steel sheet into i parts in the longitudinal direction and j parts in the width direction are within a range determined by coating adhesion, according to the value of the decarburization annealed sheet quality index at each position (m, n).

[0015] 2. The maximum O weight of the product plate is 1.00 g / m 2 and a maximum value of (Ti+V+Zr+Nb weight) / O weight is 0.01 or more.

[0016] 3. The method for producing grain-oriented electrical steel sheet according to 1 or 2 above, wherein the decarburization annealed sheet quality index is at least one of the O concentration, Si concentration, P concentration, Mn concentration, amount of SiO2 formed, amount of FeSiO3 formed, and amount of Fe2SiO4 formed on the steel sheet surface.

[0017] 4. The method for producing a grain-oriented electrical steel sheet according to any one of the above items 1 to 3, wherein the annealing separator composition contains at least one of Ti, V, Zr and Nb in an amount selected from the group consisting of Ti, V, Zr and Nb.

[0018] 5. The method for producing a grain-oriented electrical steel sheet according to any one of 1 to 4 above, wherein the finish annealing conditions are either or both of an H2 gas introduction temperature and a heating rate of 950 to 1100°C. Effect of the Invention

[0019] According to the present invention, it is possible to stably manufacture grain-oriented electrical steel sheets having excellent coating properties over their entire length and width. [Brief description of the drawings]

[0020] [Figure 1A] FIG. 2 is a diagram showing Mn fluorescent X-ray intensity at each position (m, n) of a decarburized annealed sheet in a comparative example of the present invention. [Figure 1B] FIG. 2 is a diagram showing the fluorescent X-ray Mn intensity at each position (m, n) of a decarburized annealed sheet in an example of the present invention. [Figure 2A] FIG. 2 is a diagram showing the temperature of the steel sheet surface when H2 gas is introduced during finish annealing at each position (m, n) in a comparative example of the present invention. [Figure 2B] FIG. 2 is a diagram showing the temperature of the steel sheet surface when H2 gas is introduced during finish annealing at each position (m, n) in the examples of the present invention. [Figure 3A] 1 is a diagram showing the basis weight of a product sheet O at each position (m, n) in a comparative example of the present invention. FIG. [Figure 3B] 1 is a diagram showing the basis weight of a product sheet O at each position (m, n) in an example of the present invention. FIG. [Figure 4A] FIG. 2 is a diagram showing the product sheet (Ti+V+Zr+Nb coating amount) / O coating amount at each position (m, n) in a comparative example of the present invention. [Figure 4B] FIG. 2 is a diagram showing the product sheet (Ti+V+Zr+Nb coating amount) / O coating amount at each position (m, n) in an example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] First, the steel material composition of the grain-oriented electrical steel sheet (also simply referred to as steel sheet in this specification) in the manufacturing method of the grain-oriented electrical steel sheet according to one embodiment of the present invention will be described. The steel material composition may be a conventionally known composition. Specifically, it is as follows. The balance other than the following components is Fe and unavoidable impurities. C is an effective component for improving the texture, but if the content is less than 0.01 mass%, sufficient effect cannot be obtained. On the other hand, if the content exceeds 0.1 mass%, decarburization becomes difficult and magnetic properties deteriorate. Therefore, it is preferable to set the content in the range of 0.01 to 0.1 mass%. More preferably, the lower limit is 0.02 mass% and the upper limit is 0.08 mass%.

[0022] Although Si is an effective component for increasing resistivity and improving magnetic properties, if the content is less than 1.0 mass%, sufficient effects cannot be obtained. On the other hand, if the content exceeds 5.0 mass%, cold rollability is significantly deteriorated. Therefore, it is preferable to set the content in the range of 1.0 to 5.0 mass%. More preferably, the lower limit is 2.0 mass% and the upper limit is 4.0 mass%.

[0023] Mn, like Si, increases resistivity and improves magnetic properties. It is also an effective component for improving hot ductility, but if the content is less than 0.01 mass%, sufficient effect cannot be obtained. On the other hand, if the content exceeds 0.5 mass%, the magnetic properties deteriorate. Therefore, it is preferable to set the content in the range of 0.01 to 0.5 mass%. More preferably, the lower limit is 0.02 mass% and the upper limit is 0.2 mass%.

[0024] In addition, in the present disclosure, conventionally known MnS, MnSe, or AlN can be used as an inhibitor. When MnS or MnSe is used, it is preferable to add 0.01 to 0.5 mass% of Mn, 0.002 to 0.03 mass% of S, or 0.002 to 0.03 mass% of Se. On the other hand, when AlN is used, it is preferable to add 0.004 to 0.04 mass% of Al, and 0.002 to 0.03 mass% of N. The above inhibitors may be used alone or in combination.

[0025] Furthermore, for the purpose of improving magnetic properties, one or more of the following may be added by mass: B: 0.0001-0.005%, Ti: 0.001-0.01%, P: 0.005-0.1%, Cr: 0.01-0.5%, Ni: 0.01-1.5%, Cu: 0.01-0.5%, Nb: 0.002-0.08%, Mo: 0.005-0.1%, Sn: 0.005-0.5%, Sb: 0.005-0.5%, and Bi: 0.001-0.05%.

[0026] Next, a method for producing a grain-oriented electrical steel sheet according to an embodiment of the present invention will be described. First, a steel material for grain-oriented electrical steel sheet adjusted to the above-mentioned chemical composition is subjected to hot rolling, hot-rolled sheet annealing as necessary, cold rolling once or two or more times with intermediate annealing in between, and decarburization annealing.

[0027] Here, the decarburization annealing is preferably performed at a temperature of 750 to 950°C for a time of 80 to 200 seconds. If the annealing temperature is less than 750°C and the annealing time is less than 80 seconds, decarburization may be difficult. On the other hand, if the annealing temperature is more than 950°C and the annealing time is more than 200 seconds, the primary recrystallized grain size may become coarse and secondary recrystallization may be suppressed, resulting in deterioration of magnetic properties.

[0028] The oxidation ratio (PH2O / PH2) of the decarburization annealing is preferably in the range of 0.3 to 0.6. If PH2O / PH2 is less than 0.3, decarburization may be difficult. On the other hand, if PH2O / PH2 exceeds 0.6, FeO may be formed, which may deteriorate the coating properties.

[0029] In this embodiment, it is important to obtain data on the quality index of the decarburized annealed steel sheet (in this example, obtained by calculation or measurement) because this contributes to determining the finish annealing conditions. The decarburized annealed sheet quality indexes are, for example, the O concentration, Si concentration, P concentration, and Mn concentration on the steel sheet surface, the amount of SiO2, FeSiO3, and Fe2SiO4 formed, etc. Furthermore, the ratio of any of these concentrations or amounts may be determined and used. When the decarburized annealed sheet quality indexes are obtained by measurement, they may be obtained by measurement using X-ray fluorescence analysis, infrared spectroscopy, etc., and when they are obtained by calculation, they may be obtained by calculation from the decarburized annealing conditions such as the annealing temperature, time, and oxidation degree.

[0030] Then, the steel sheet surface is coated with an annealing separator mainly composed of MgO. Here, at least one of Ti, Zr, V, and Nb compounds is added to the annealing separator for the purpose of improving the coating properties. The total amount of these added is preferably 1 to 7 mass% in terms of each metal element. If the amount added is less than 1 mass%, sufficient effect cannot be obtained. On the other hand, if the amount added exceeds 7 mass%, each metal element may penetrate into the steel, and the magnetic properties may deteriorate. The type of compound is not limited. For example, oxides, hydroxides, borates, carbonates, nitrates, phosphates, sulfates, halides, etc. can be used. These may be used alone or in combination. It is preferable to record data on the composition of the applied annealing separator since this data will be used later when creating a prediction model.

[0031] Furthermore, for the purpose of improving the film properties and magnetic properties, conventionally known oxides, hydroxides, borates, carbonates, nitrates, phosphates, sulfates, and halides of Li, Na, Mg, Al, Si, K, Ca, Fe, Co, Ni, Cu, Sr, Ba, and lanthanides may be added. These may be used alone or in combination.

[0032] The amount of these additives is preferably in the range of 0.01 to 15 parts by mass relative to 100 parts by mass of MgO. If the amount is less than 0.01 part by mass, sufficient effects cannot be obtained. On the other hand, if the amount is more than 15 parts by mass, excessive film formation or excessive suppression may occur, which may deteriorate the magnetic properties. Then, a final anneal is applied, which may include a secondary recrystallization anneal for promoting secondary recrystallization, and a purification anneal for purifying the inhibitor.

[0033] In the above secondary recrystallization annealing, when the secondary recrystallization is to be completed during soaking, the annealing temperature is preferably 800 to 1000°C and the annealing time is preferably in the range of 5 to 200 hours. If the annealing temperature is less than 800°C or the annealing time is less than 5 hours, the secondary recrystallization may not be completed during soaking, and the magnetic properties may deteriorate. On the other hand, if the annealing temperature exceeds 1000°C or the annealing time exceeds 200 hours, the coil may buckle and the shape may deteriorate.

[0034] In addition, when the secondary recrystallization is completed during heating, the heating rate at 700 to 1100°C is preferably in the range of 2.5 to 50°C / h. If the heating rate is less than 2.5°C / h, the coil may buckle and the shape may deteriorate. On the other hand, if the heating rate exceeds 50°C / h, the secondary recrystallized grains may become fine and the magnetic properties may deteriorate. Here, the annealing atmosphere is an inert atmosphere of N2 or Ar.

[0035] In the purification annealing, the annealing temperature is preferably 1150 to 1250°C and the annealing time is preferably in the range of 2 to 50 hours. If the annealing temperature is less than 1150°C or the annealing time is less than 2 hours, the purification may be insufficient. On the other hand, if the annealing temperature is more than 1250°C or the annealing time is more than 50 hours, the coil may buckle and the shape may deteriorate.

[0036] In addition, for the purpose of accelerating the formation of the coating and purification, H2 gas is introduced at a temperature in the range of 900 to 1050°C. By introducing H2 gas, the Fe oxide formed on the steel sheet surface is reduced, the oxidation in the furnace increases, and the formation of the coating is accelerated. If the H2 gas introduction temperature is less than 900°C, the inhibitor may decompose before the secondary recrystallization is completed, and the magnetic properties may deteriorate. On the other hand, if the H2 gas introduction temperature exceeds 1050°C, sufficient effect cannot be obtained.

[0037] In this embodiment, data on the finish annealing conditions of the steel sheet is obtained (in this example, obtained by calculation or measurement), because it directly affects the coating properties. The above-mentioned finish annealing conditions are either or both of the H2 gas introduction temperature and the heating rate between 950 and 1100° C. When the above-mentioned finish annealing conditions are obtained by measurement, they may be obtained by actual measurement with a thermocouple wound in a coil, or when they are obtained by calculation, they may be obtained by calculation from the finish annealing conditions such as the annealing temperature and time.

[0038] Furthermore, in this embodiment, it is important to obtain data on the weight of O and the weight of Ti+V+Zr+Nb contained in the forsterite coating of the product sheet (obtained by measurement in this example), because the magnitude of the weight of O allows an index related to peeling resistance (coating adhesion), which is the most important of the coating properties, to be estimated with good reproducibility, leading to non-destructive management of the coating properties of the steel sheet.

[0039] Regarding acquisition by measurement, a method for non-destructively measuring the basis weight of each element includes, for example, a method in which the fluorescent X-ray intensity of each element is measured and then converted to the basis weight of each element using a calibration curve created in advance.

[0040] In the method according to the present embodiment, first, data on the decarburization annealed sheet quality index and the finish annealing conditions of the steel sheet are obtained, and data on the weight of O and the weight of Ti+V+Zr+Nb contained in the forsterite coating of the product sheet are also obtained. Next, a prediction model for each basis weight is created by performing multiple regression analysis or machine learning using the actual values ​​of each basis weight as the objective variable and the actual values ​​of the decarburized annealed sheet quality index, the annealing separator composition, and the finish annealing conditions as explanatory variables.

[0041] Furthermore, the steel plate to be subjected to the manufacturing method of this embodiment is divided into i parts in its longitudinal direction and further divided into j parts in its width direction, and each position (m, n) (where 1≦m≦i, 1≦n≦j) is set. Then, using the prediction model for each coating weight, the annealing separator composition and finish annealing conditions are substituted within a certain range for the decarburization annealed sheet quality index at each of the positions (m, n), and the annealing separator composition and finish annealing conditions are set so that the maximum O coating weight and the maximum (Ti+V+Zr+Nb coating weight) / O coating weight at each of the positions (m, n) are within a range determined by the coating adhesion.

[0042] That is, in this embodiment, when using the prediction model for each basis weight, the decarburization annealed sheet quality index, finish annealing conditions, and each basis weight of the product sheet are used at each position (m, n) (where 1≦m≦i, 1≦n≦j) obtained by dividing the steel sheet longitudinal direction into i parts and the steel sheet width direction into j parts. Each position (m, n) indicates each divided region (portion) when the steel plate is divided into i portions in the longitudinal direction, preferably 10 to 100 portions, and into j portions in the width direction, preferably 5 to 20 portions.

[0043] Furthermore, when creating a prediction model for each of the coating weights, the decarburization annealed sheet quality index and the finish annealing conditions for the steel sheet are obtained (e.g., derived by calculation or measurement), and the O coating weight and Ti+V+Zr+Nb coating weight contained in the forsterite coating of the product sheet are obtained (e.g., derived by measurement), the steel sheet may be divided into i parts in the longitudinal direction and j parts in the width direction of the steel sheet and obtained (e.g., such calculation or measurement may be performed).

[0044] When the O, Si, P and Mn concentrations on the surface of the decarburized annealed sheet are high, or when the amount of Fe-based oxides such as FeSiO3 and Fe2SiO4 is high, the coating formation during the final annealing becomes excessive, and the O weight after the final annealing increases. As a result, the (Ti+V+Zr+Nb weight) / O weight may become insufficient. Therefore, it is necessary to suppress the coating formation during the final annealing by increasing the H2 gas introduction temperature during the final annealing and / or slowing down the heating rate between 950 and 1100°C. Furthermore, it is necessary to increase the Ti+V+Zr+Nb weight by reducing the O weight and / or increasing the amount of Ti, V, Zr and Nb added to the annealing separator.

[0045] On the other hand, when the O, Si, P, and Mn concentrations on the surface of the decarburized annealed sheet are low, or when the amount of Fe-based oxides such as FeSiO3 and Fe2SiO4 is small, the formation of the coating during the final annealing may be insufficient, resulting in a risk of an insufficient O weight after the final annealing. Therefore, it is necessary to promote the formation of the coating during the final annealing and increase the O weight by lowering the H2 gas introduction temperature during the final annealing and / or by increasing the heating rate between 950°C and 1100°C.

[0046] Note that the model used in the machine learning used in this embodiment is not limited. A random forest or a neural network may be used.

[0047] Thereafter, if necessary, insulating coating, flattening annealing, and magnetic domain refinement are performed to produce a finished sheet. Note that the Ti fluorescent X-ray intensity of the finished sheet may be measured according to the above-mentioned procedure at any time before the finishing annealing and production of the finished sheet.

[0048] Here, the maximum range of the O basis weight is 1.00 g / m 2 It is preferable that the amount is equal to or more than that. Maximum weight per unit area is 1.00g / m 2 If the coating amount is less than 2.00 g / m, the amount of the coating formed is too small, and the coating may be easily broken by external stress, resulting in insufficient adhesion. 2 The upper limit of the range of the maximum number of the O basis weight is not particularly limited, but it is set to 10.00 g / m because it will cause a decrease in the space factor. 2 It is preferable that the temperature is less than 100°C.

[0049] Moreover, the maximum range of the (Ti+V+Zr+Nb weight) / O weight is preferably 0.01 or more. If the value of the maximum number of (Ti+V+Zr+Nb weight) / O weight is less than 0.01, the coating adhesion may be insufficient. More preferably, it is 0.02 or more. Although there is no particular upper limit to the range of the maximum number of (Ti+V+Zr+Nb weight) / O weight, it is preferable that it is about 0.20 or less because there is a risk of each metal element penetrating into the steel.

[0050] The reason why coating adhesion can be evaluated by the value of (Ti+V+Zr+Nb weight) / O weight of the finished sheet is not clear, but the inventors think as follows. That is, the Ti, V, Zr, and Nb compounds added to the annealing separator decompose during final annealing, and are incorporated into the forsterite coating in the form of nitrides or oxides, etc., and segregate at grain boundaries, thereby increasing the strength of the coating. Therefore, it is believed that the greater the weight of Ti+V+Zr+Nb relative to the amount of forsterite coating, the better the coating adhesion. Therefore, it is believed that the adhesion of the forsterite coating (coating adhesion) can be evaluated by measuring the (Ti+V+Zr+Nb coating weight) / O coating weight, which allows estimation of such grain boundary segregation. In the above example, the data of the decarburized annealed sheet quality index and the finish annealing conditions of the steel sheet are measured or calculated, and further, the data of the O weight and the Ti+V+Zr+Nb weight contained in the forsterite coating of the product sheet are measured. However, the present disclosure is not limited to this case. For example, when past actual value data exists, such a series of data can be obtained from the outside. As an example, a series of data can be obtained by a communication unit of a computer. Alternatively, such a series of data can be obtained by a human being through transfer or the like. Also, for example, in the case of the finish annealing conditions, data of the set value can be obtained instead of calculation or measurement. In this way, the acquisition of data necessary for creating a learning model can be variously modified or changed. EXAMPLES

[0051] [Example 1] In this embodiment, a general machine learning tool was used to create a prediction model for each coating weight by machine learning using a neural network, with the actual values ​​of the product sheet O coating weight and Ti+V+Zr+Nb coating weight over the past two years as the objective variables, and the actual values ​​of the decarburized annealed sheet quality index, annealing separator composition, and finish annealing conditions as explanatory variables.

[0052] A steel material containing, by mass%, 0.03% C, 0.004% N, 0.007% Al, 3.4% Si, and 0.06% Mn, with the remainder being Fe and unavoidable impurities, was slab heated at 1260°C, hot rolled, and further cold rolled, and then intermediate annealed at 1050°C for 1 minute and cold rolled again to obtain a 0.23 mm thick cold rolled sheet. The sheet was then decarburized in a wet hydrogen atmosphere at 840°C for 2 minutes, and then divided into 50 sections (i) at 100 m pitches in the longitudinal direction of the steel sheet and 10 sections (j) at 100 mm pitches in the width direction of the steel sheet. X-ray fluorescence analysis and infrared spectroscopy were performed at each position (m, n) (where 1≦m≦i, 1≦n≦j) to measure the intensity of each element and the amount of each oxide generated at each position (m, n) of the steel sheet. Next, an annealing separator containing 100 parts by mass of MgO and 3 parts by mass of TiO2 was applied, and the material was subjected to a soaking treatment at 850°C for 50 hours in a N2 gas atmosphere. The material was then heated in the range of 950 to 1100°C at a heating rate of 15°C / h, H2 gas was introduced at the specified temperature, and the material was subjected to a soaking treatment at 1200°C for 5 hours.

[0053] Here, the maximum weight of the product sheet O at each position (m, n) is 1.00 g / m 2 Finish annealing was performed under the conditions of the present invention, in which the H gas introduction temperature for each of the 10 coils was adjusted within the range of 900 to 1050°C so that the maximum ratio of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more, and the condition in which the H gas introduction temperature for all 10 coils was set to 960°C. After that, a coating mainly made of phosphate was applied, and then flattening annealing was performed at 850°C for 1 minute to produce the finished product sheet.

[0054] The product plate thus obtained was subjected to fluorescent X-ray analysis at each position (m, n) to measure the fluorescent X-ray O, Ti, V, Zr and Nb intensities, and converted into each basis weight using a calibration curve. The maximum O basis weight was 1.00 g / m 2 The percentage of positions where the maximum number of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more was determined. Here, the following Tables 1-1 to 8-2 show a comparison of the case where the H2 gas introduction temperature during finish annealing is changed to 980°C in accordance with the present invention and the case where it is uniformly set to 960°C when the fluorescent X-ray Mn intensity at the end of the decarburized annealed sheet is high.

[0055] [Table 1-1]

[0056] [Table 1-2]

[0057] [Table 2-1]

[0058] [Table 2-2]

[0059] [Table 3-1]

[0060] [Table 3-2]

[0061] [Table 4-1]

[0062] [Table 4-2]

[0063] [Table 5-1]

[0064] [Table 5-2]

[0065] [Table 6-1]

[0066] [Table 6-2]

[0067] [Table 7-1]

[0068] [Table 7-2]

[0069] [Table 8-1]

[0070] [Table 8-2]

[0071] As shown in Tables 1-1 to 8-2 and Figures 1A, 1B, 2A, 2B, 3A, 3B, 4A, and 4B, when the H2 gas introduction temperature was changed to 980°C in response to the high Mn fluorescent X-ray intensity of the decarburized annealed sheet at the steel sheet width direction end, excessive coating formation at the upper part of the coil could be effectively prevented. As a result, the maximum O weight of the product sheet was 1.00 g / m 2Furthermore, the percentage of positions where the maximum number of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more increased (in the example of Fig. 4B, the percentage was 100%). On the other hand, when the H2 gas inlet temperature was set to a uniform 960°C, excessive film formation occurred at the top of the coil, and the maximum number of O weights on the product plate was 1.00 g / m 2 Furthermore, the percentage of positions where the maximum number of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more decreased (in the example of FIG. 4A, the percentage was 75.4%).

[0072] In this way, when the H2 gas introduction temperature was changed according to the variation in the quality index of the decarburized annealed sheet (invention example), the maximum number of O weights of the product sheet was 1.00 g / m 2 The percentage of positions where the maximum number of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more was 98.8% on average for the 10 coils. In contrast, when the H2 gas introduction temperature was uniformly set to 960°C (Comparative Example), the percentage was 86.6% on average for the 10 coils.

[0073] [Example 2] In this embodiment, a general machine learning tool was used to create a prediction model for each coating weight by machine learning using random forest, with the actual values ​​of the product sheet O coating weight and Ti+V+Zr+Nb coating weight over the past two years as the objective variables, and the actual values ​​of the decarburized annealed sheet quality index, annealing separator composition, and finish annealing conditions as explanatory variables.

[0074] A material containing, by mass%, 0.07% C, 0.009% N, 0.022% Al, 3.4% Si, 0.07% Mn, and 0.02% Se, with the remainder being Fe and unavoidable impurities, was slab heated at 1380°C, hot rolled, cold rolled, intermediate annealed at 1050°C for 1 minute, and cold rolled again to obtain a 0.23 mm cold rolled sheet. The sheet was then decarburized and annealed in a wet hydrogen atmosphere at 840°C for 2 minutes, and then divided into 50 sections (i) at 100 m pitches in the longitudinal direction of the steel sheet and 10 sections (j) at 100 mm pitches in the width direction of the steel sheet. X-ray fluorescence analysis and infrared spectroscopy were performed at each position (m, n) (where 1≦m≦i, 1≦n≦j) to measure the intensity of each element and the amount of each oxide generated at each position (m, n) of the steel sheet. Thereafter, an annealing separator containing 100 parts by mass of MgO and 3 parts by mass of TiO2 was applied, and the material was heated in the range from room temperature to 950°C at a heating rate of 15°C / h, and then heated in the range from 950 to 1100°C at a prescribed heating rate. H2 gas was then introduced at 950°C, and the material was soaked at 1200°C for 5 hours.

[0075] Here, according to the quality index of the decarburized annealed sheet at each position (m, n), the maximum number of O weights of the product sheet at each position (m, n) is 1.00 g / m 2 Finish annealing was performed in each of the 10 coils, with the heating rate from 950 to 1100°C changed to 10 to 20°C / h for each, and in each of the 10 coils set to a uniform rate of 15°C / h for all 10 coils, so that the maximum value of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more. A phosphate-based coating was then applied, and flattening annealing was performed at 850°C for 1 minute to produce a finished product sheet. X-ray fluorescence analysis was then performed at each position (m, n) of the finished product sheet, and the X-ray fluorescence intensities of O, Ti, V, Zr and Nb were measured and converted to each weight using the calibration curve, and the maximum O weight was determined to be 1.00 g / m 2 The percentage of positions where the maximum number of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more was determined.

[0076] When the heating rate is changed according to the variation in the quality index of the decarburized annealed sheet, the maximum O weight of the product sheet is 1.00 g / m 2The percentage of positions where the maximum ratio of (Ti+V+Zr+Nb weight) / O weight was 0.01 or more was 98.7% on average for the 10 coils. In contrast, when the heating rate was set uniformly at 15℃ / h, the percentage was 84.3% on average for the 10 coils.

Claims

1. A method for producing grain-oriented electrical steel sheet, comprising the steps of hot rolling a steel material for grain-oriented electrical steel sheet, cold rolling once or at least twice with intermediate annealing therebetween, decarburization annealing, applying an annealing separator mainly composed of MgO to the surface of the steel sheet, and finish annealing the steel sheet to obtain a finished sheet, comprising the steps of: Data on the quality index of the decarburization annealed steel sheet and the finish annealing conditions are obtained, and data on the weight of O and the weight of Ti+V+Zr+Nb contained in the forsterite coating of the product sheet are further obtained, a prediction model for each basis weight is created by performing multiple regression analysis or machine learning using the actual values ​​of each basis weight as a response variable and the decarburization annealed sheet quality index, the annealing separator composition, and the actual values ​​of the finish annealing conditions as explanatory variables; A manufacturing method for grain-oriented electrical steel sheet, in which a prediction model for each of the aforementioned coating weights is used, and according to the value of the decarburization annealed sheet quality index at each position (m, n) (where 1≦m≦i, 1≦n≦j, 10≦i≦100, 5≦j≦20) obtained by dividing the steel sheet into i parts in the longitudinal direction and j parts in the width direction, the annealing separator composition and the finish annealing conditions are set so that the O coating weight and (Ti+V+Zr+Nb coating weight) / O coating weight at each position (m, n) are within ranges determined by coating adhesion.

2. The maximum O weight of the product sheet is 1.00 g / m 2 and a maximum number of (Ti+V+Zr+Nb weight) / O weight is 0.01 or more.

3. The decarburization annealed sheet quality index is O concentration, Si concentration, P concentration, Mn concentration, SiO 2 Production amount, FeSiO 3 Amount of production, and Fe 2 SiO 4 The method for producing a grain-oriented electrical steel sheet according to claim 1 or 2, wherein at least one of the amounts of the grains produced is a grain boundary grain.

4. 3. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein the annealing separator composition is at least one of an amount of Ti, an amount of V, an amount of Zr, and an amount of Nb contained in the annealing separator.

5. The method for producing a grain-oriented electrical steel sheet according to claim 3, wherein the annealing separator composition is at least one of an amount of Ti, an amount of V, an amount of Zr, and an amount of Nb contained in the annealing separator.

6. The finish annealing conditions are: 2 The method for producing a grain-oriented electrical steel sheet according to claim 1 or 2, wherein either or both of the gas introduction temperature and the heating rate are 950 to 1100°C.

7. The finish annealing conditions are: 2 The method for producing a grain-oriented electrical steel sheet according to claim 3, wherein either or both of the gas introduction temperature and the heating rate are 950 to 1100°C.

8. The finish annealing conditions are: 2 The method for producing a grain-oriented electrical steel sheet according to claim 4, wherein either or both of the gas introduction temperature and the heating rate are 950 to 1100°C.

9. The finish annealing conditions are: 2 The method for producing a grain-oriented electrical steel sheet according to claim 5, wherein either or both of the gas introduction temperature and the heating rate are 950 to 1100°C.

Citation Information

Patent Citations

  • Preparation of unidirectional silicon steel plate

    JP1984193220A

  • Method for controlling amount of oxide film at decarburizing annealing for grain oriented silicon steel sheet

    JP1996100220A

  • Forsterite film of grain oriented silicon steel sheet with high magnetic flux density and its formation

    JP1997184017A

  • Oxide coating film adhesion strength evaluation method and its evaluation device of directional electromagnetic steel plate

    JP2011158328A

  • Oriented electrical steel sheet and method therefor

    JP2016145419A